Incidence of Helicobacter pylori in patients with upper gastrointestinal symptoms: a hospital-based study - Jamdade, Pundlik; Shinde, Swapnil; Chawada, Meghraj J.; Deshmukh, Sudhir B. (International Surgery Journal, 2021)
Background: Commonest complaints for which patients seek hospital care are upper gastrointestinal (UGI) symptoms. Prevalence of these symptoms range from 8-54%. Most common cause is Helicobacter pylori. The objective of this study was to investigate incidence of Helicobacter pylori in patients with UGI symptoms. Methods: Hospital-based study was carried out among 200 cases with esophageal disorders, gastric disorders, duodenal disorders, gastro duodenitis. Predesigned and pretested questionnaire was used to record information. Gastric and duodenal biopsy was taken. Rapid antigen test kit was used to identify for Helicobacter pylori. Results: Incidence of Helicobacter pylori was 80%. Most common disorders associated with UGI symptoms were gastritis (29%), gastritis with duodenal ulcer (21%) and esophagitis (21%). They were more common in males except esophageal varices. Gastritis and esophagitis were significantly more in 21-40 years (46.55%) (p<0.05). Most common age of UGI symptoms was 21-40 years (34.5%). H. pylori infection was more among males (62.50%). Most common indication for endoscopy was dyspepsia in 48 (24%). Conclusions: Incidence of H. pylori was 80%. Upper GI diseases are more common in men (65.5%) compared to females (34.5%) with the most affected age group between 21-60 years (68%). H. pylori was the commonest cause of chronic gastroduodenitis in this study.